Preparation method of modified aramid fiber, modified aramid fiber and modified asphalt

By performing surface modification of CaCl2 and coupling agent on aramid fiber, the problem of poor adhesion performance in asphalt mixture is solved, the better combination of modified aramid fiber and asphalt is achieved, and the performance of modified asphalt is improved.

CN118621571BActive Publication Date: 2025-03-07TIANHE COLLEGE GUANGDONG POLYTECHNIC NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410773886.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-17
Publication Date
2025-03-07
Estimated Expiration
2044-06-17

AI Technical Summary

Technical Problem

Aramid fibers have poor adhesion performance, electrostatic adsorption and agglomeration and entanglement in asphalt mixtures, resulting in poor application effect in asphalt roads.

Method used

By dissolved compounds such as CaCl2 and coupling agent KH550 in an organic solvent, soaking and drying it with aramid fibers to form modified aramid fibers, and enhancing its surface chemical activity and dispersion.

Benefits of technology

The adhesion performance of modified aramid fibers is significantly improved, dispersibility is enhanced, and the surface roughness is increased, which can better combine with asphalt and improve the overall performance of modified asphalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118621571B_ABST
    Figure CN118621571B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fiber materials and provides a method for preparing modified aramid fiber. The method comprises the following steps: step 1: providing aramid fiber; step 2: dissolving a complex in a first organic solvent to obtain a first mixed solution, adding the aramid fiber to the first mixed solution, and performing a drying process after soaking for 8-48 hours; step 3: dissolving a compound of formula I in a second organic solvent to obtain a second mixed solution, adding the product obtained in step 2 to the second mixed solution, and performing a drying process after soaking for 1-4 hours to obtain the modified aramid fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of asphalt roads, and in particular to a preparation method of modified aramid fiber, the modified aramid fiber and modified asphalt. Background Art

[0002] Asphalt materials have a wide range of applications, such as in ground, houses, coatings, etc. Asphalt has been widely used in the construction industry and has good waterproofness and durability. Modern civil engineering requires not only good performance of asphalt, but also a long service life, but asphalt materials are greatly affected by the environment and are prone to aging. In order to improve the performance of asphalt and meet the quality indicators required by the project, people use methods such as blending and adding admixtures to prepare various modified asphalts to meet the needs of the project and achieve better use requirements. Although the promotion of modified asphalt has improved its performance, it has failed to change the adhesion and weather resistance of asphalt, so it is difficult to meet market demand.

[0003] As a kind of high molecular weight flexible synthetic fiber, aramid fiber has excellent properties such as ultra-high strength, high modulus, high temperature resistance, acid and alkali resistance, and light weight, and is widely used in the aviation and automotive fields. In order to improve the performance and life of asphalt pavement, scholars and engineers in the field of asphalt roads have paid attention to the characteristics of aramid, which is light, high-strength and heat-resistant, and have conducted scientific research and practical engineering application research. At present, the research on aramid in the field of asphalt roads is mainly carried out around aramid fibers and aramid combined fibers (such as polyolefin: aramid = 86:14). In the study, it was found that after aramid fibers were added to asphalt mixtures, there was a phenomenon of agglomeration and entanglement, which had a negative impact on the performance of asphalt mixtures.

[0004] Due to the high crystallinity of the aramid fiber molecular chain, the fiber surface is smooth and the chemical activity is poor, and the adhesion between aramid fiber and most polymer matrices is poor. In addition, due to the high water absorption of aramid fiber, the use of aramid fiber to prepare asphalt mixture is likely to have a negative impact on the water stability of the mixture. Therefore, in the application of asphalt concrete, short-cut aramid fiber often has poor adhesion to the asphalt matrix, and is prone to fiber peeling under long-term erosion by external rainwater. The polarity of aramid itself will also cause mutual adsorption between fiber bundles. To solve these problems, researchers often use methods such as surface etching and chemical modification to enhance the surface roughness and chemical activity of the fiber to solve these defects. Among them, the use of coupling agents to modify the fiber surface is currently the most widely used, most widely studied, and economical method.

[0005] CN105802041A discloses an additive for asphalt pavement construction and a preparation method thereof. When in use, the additive is mixed with existing asphalt concrete before construction, so that the road surface after construction has higher strength and wear resistance, and can greatly improve the service life of the paved asphalt pavement; however, it is necessary to add reinforcing particles, reinforcing fibers and auxiliary agents, the reinforcing particles are obtained by sintering and grinding kaolin, clay, coal gangue, aluminum ash, red mud, elemental silicon powder and metal powder, and the reinforcing fibers are a mixture of polyacrylonitrile fibers, aramid fibers and epoxy resin; the method is complicated to operate and has a high cost.

[0006] CN106147255A discloses a highly efficient anti-aging modified asphalt with good high-temperature stability, which comprises polypropylene, sodium stearate, hexadecyltrimethylammonium bromide, mixed asphalt, magnesium dialkyl sulfonate succinate, polyurethane, Sasobit polyolefin, phosphorus pentasulfide, organic pigment, antioxidant, aliphatic polyurethane resin, serpentine, mica powder, rubber, aramid pulp and silicon carbide whisker, which prevents low-temperature cracking, has good heat resistance and anti-aging properties, improves wear resistance and extends service life; however, its cost is still relatively high.

[0007] Summarizing the existing methods for modifying the surface of aramid fibers, it can be found that, due to its chemical inertness, various complexing agents need to be used to form a new chemical surface before modification with coupling agents. Therefore, in order to solve the shortcomings of poor adhesion between aramid fibers and asphalt, electrostatic adsorption between fibers, and easy agglomeration in asphalt, CaCl2 and coupling agents are used to treat the surface of aramid fibers. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing modified aramid fiber, so as to solve the chemical inertness of the surface of aramid fiber and make it better applied in asphalt roads.

[0009] To achieve the above-mentioned purpose of the invention, the technical solution of the present invention is as follows:

[0010] The present invention provides a method for preparing modified aramid fiber, the method comprising the following steps:

[0011] Step 1: Providing aramid fiber;

[0012] Step 2: dissolving the complex in a first organic solvent to obtain a first mixed solution, adding the aramid fiber to the first mixed solution, soaking for 8-48 hours and then performing a drying process;

[0013] Step 3: dissolving the compound of formula I in a second organic solvent to obtain a second mixed solution, and adding the product obtained in step 2 to the second mixed solution, soaking for 1-4 hours and then performing a drying process to obtain the modified aramid fiber.

[0014] In one aspect of the invention, the complex comprises at least one compound having the chemical formula MCl x A compound wherein x is selected from an integer of 1 to 4, and M is selected from Li, Ca, Al, Ga, In, Sn, Sb, Ti, Mn, Fe, Ni, Co or Cu.

[0015] In one aspect of the present invention, the compound of formula I comprises at least one compound having the following structure:

[0016]

[0017] T1 is selected from Si, Ti or Al; n1 is selected from an integer of 1-5;

[0018] n1 A's are the same as or different from each other, and A is selected from a halogen atom, a hydroxyl group, a nitro group, a cyano group, an amino group, a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C1-C10 cycloalkyloxy group, a substituted or unsubstituted C3-30 cycloalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted 3-30-membered heterocyclyl group, a substituted or unsubstituted 5-30-membered heteroaryl group, or a substituted or unsubstituted 3-30-membered ring formed by bonding with an adjacent substituent;

[0019] n1 R1s are the same as or different from each other, and R1 is selected from a direct bond, a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, or a substituted or unsubstituted C1-C10 cycloalkoxy group;

[0020] n1 T2 are the same or different from each other, and T2 is selected from a direct bond, an alkoxy group, a carboxyl group, a sulfoxy group, a phosphoryl group, a phosphite group or a pyrophosphoryl group;

[0021] R2 is selected from a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C1-C10 cycloalkyloxy group, a substituted or unsubstituted C3-30 cycloalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted 3-30 membered heterocyclyl group, or a substituted or unsubstituted 5-30 membered heteroaryl group; R3 is selected from a direct bond or a substituted or unsubstituted C1-C30 alkyl group.

[0022] In one aspect of the invention, the complex is selected from CaCl2 and / or LiCl2.

[0023] In one aspect of the invention, the complex is selected from CaCl2.

[0024] In one aspect of the present invention, the first organic solvent is selected from anhydrous ethanol.

[0025] In one aspect of the present invention, in the first mixed solution, based on the total mass of the first mixed solution, the mass percentage of the complex is selected from 3% to 8%.

[0026] In one aspect of the present invention, in the first mixed solution, based on the total mass of the first mixed solution, the mass percentage of the complex is selected from 5%.

[0027] In one aspect of the present invention, in step 2, the soaking time is selected from 18-28 hours.

[0028] In one aspect of the present invention, in step 2, the soaking time is selected from 20-26 hours.

[0029] In one aspect of the present invention, in step 2, the soaking time is selected from 24 hours.

[0030] In one aspect of the present invention, the second organic solvent is selected from a mixed solution of anhydrous ethanol and water, and the mass ratio of the anhydrous ethanol to water is selected from (6-8): (2-4).

[0031] In one aspect of the present invention, the second organic solvent is selected from a mixed solution of anhydrous ethanol and water, and the mass ratio of the anhydrous ethanol to water is selected from 7:3.

[0032] In one aspect of the present invention, in the second mixed solution, based on the total mass of the second mixed solution, the mass percentage of the compound of formula I is selected from 1%-2%.

[0033] In one aspect of the present invention, in the second mixed solution, the mass ratio of anhydrous ethanol, water and the compound of formula I is 7:3:(0.01-0.02).

[0034] In one aspect of the present invention, the drying process is carried out at 85°C-105°C, and the drying time is selected from 1.5-3h.

[0035] In one aspect of the present invention, the drying process is natural air drying.

[0036] In one aspect of the present invention, the compound of formula I is selected from silane coupling agent KH550 and / or silane coupling agent KH560.

[0037] In one aspect of the present invention, there is provided a method for preparing modified aramid fiber, the method comprising the following steps:

[0038] Step 1: Providing aramid fiber;

[0039] Step 2: dissolving CaCl2 and / or LiCl2 in anhydrous ethanol to obtain a first mixed solution, wherein the mass percentage of CaCl2 and / or LiCl2 is selected from 5%, adding the aramid fiber to the first mixed solution, soaking for 8-48 hours, filtering, and then placing in a ventilated oven at a temperature of 85°C-105°C and drying for 1.5-3 hours;

[0040] Step 3: dissolving silane coupling agent KH550 and / or silane coupling agent KH560 in a second organic solvent, wherein the second organic solvent is a solution of anhydrous ethanol and water in a mass ratio of 7:3, to obtain a second mixed solution, wherein the mass percentage of silane coupling agent KH550 and / or silane coupling agent KH560 is selected from 1%-2%, and adding the product obtained in step 2 to the second mixed solution, soaking for 2-3 hours, filtering, and then placing in a ventilated oven at a temperature of 85°C-105°C, and drying for 1.5-3 hours to obtain the modified aramid fiber.

[0041] The present invention provides a modified aramid fiber, and the modified aramid fiber is obtained by the above method for preparing the modified aramid fiber.

[0042] The present invention provides a modified asphalt, which comprises the aforementioned modified aramid fiber, base asphalt and a modified material.

[0043] In one aspect of the present invention, based on the total mass of the modified asphalt, the mass percentage of the modified aramid fiber is selected from 0.1% to 10%.

[0044] The present invention provides application of the above method for preparing modified aramid fiber in asphalt roads.

[0045] The beneficial effects of the present invention are:

[0046] (1) The modified aramid fiber obtained by the method for preparing modified aramid fiber provided by the present invention reduces the polarity of the aramid fiber, improves the dispersibility of the aramid fiber, enhances the chemical activity, fiber oil absorption rate and surface roughness of the aramid fiber, and improves the adhesion performance between the aramid fiber and asphalt, thereby improving the performance of the modified asphalt containing the modified aramid fiber.

[0047] (2) The method for preparing modified aramid fiber provided by the present invention has fewer steps, requires less energy during the modification process, and requires a lower concentration of the solution containing the coupling agent, so it is economical.

[0048] (3) All steps of the method for preparing modified aramid fiber provided by the present invention are carried out at room temperature and do not require an additional heating process. Therefore, the method is simple, environmentally friendly and efficient, and is more conducive to large-scale promotion and application in the engineering field. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The present invention is a flow chart of the method for preparing modified aramid fiber.

[0050] Figure 2 This is a mechanism diagram of the method for preparing modified aramid fiber of the present invention.

[0051] Figure 3 It is the infrared spectra of Examples 1-5 and Comparative Example 1 of the present invention.

[0052] Figure 4 The infrared spectra of Examples 3, 6-8 and Comparative Examples 1-2 of the present invention are shown.

[0053] Figure 5 It is a high temperature rheological performance diagram of Examples 3, 6-8 of the present invention and Comparative Examples 1-2.

[0054] Figure 6 The microscopic morphology of the fiber surface before and after modification of the present invention.

[0055] Figure 7 This is a comparison chart of the dispersion of fibers in asphalt before and after modification of the present invention.

[0056] Figure 8 It is a comparison chart of high temperature anti-rutting performance of Example 1 of the present invention and Comparative Example 1.

[0057] Fig. 9 It is a comparison chart of the low temperature crack resistance of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0058] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present application.

[0059] In the present invention, the term "alkyl" refers to an aliphatic hydrocarbon group, which can be straight or branched. Branched refers to one or more lower alkyl groups, such as methyl, ethyl or propyl, attached to a linear alkyl chain. "Lower alkyl" refers to a group containing about 1 to about 6 carbon atoms in the chain, which can be straight or branched.

[0060] In the present invention, the term "alkenyl" refers to an aliphatic hydrocarbon group containing at least one carbon-carbon double bond, which can be straight or branched. Branched refers to one or more lower alkyl groups, such as methyl, ethyl or propyl, attached to a linear alkenyl chain. "Lower alkenyl" refers to a group containing about 2 to about 6 carbon atoms in the chain, which can be straight or branched.

[0061] In the present invention, the term "alkynyl" refers to an aliphatic hydrocarbon group containing at least one carbon-carbon triple bond, which can be straight or branched. Branched refers to one or more lower alkyl groups, such as methyl, ethyl or propyl, attached to a linear alkynyl chain. "Lower alkynyl" refers to containing about 2 to about 6 carbon atoms in the chain, which can be straight or branched. Non-limiting examples of alkynyl include ethynyl, propynyl, 2-butynyl, 3-methylbutynyl, n-pentynyl and decynyl.

[0062] In the present invention, the term "aryl" refers to an aromatic monocyclic or polycyclic ring system. The aryl group may be optionally substituted with one or more "ring system substituents", which may be the same or different, and are as defined herein. Non-limiting examples of suitable aryl groups include phenyl and naphthyl.

[0063] In the present invention, the term "heteroaryl" refers to an aromatic monocyclic or polycyclic ring system in which one or more of the ring atoms is an element other than carbon, such as nitrogen, oxygen or sulfur, either alone or in combination, preferably containing about 5 to about 6 ring atoms. The "heteroaryl" may be optionally substituted with one or more "ring system substituents", which may be the same or different, as defined herein. The prefix aza, oxa or thia before the heteroaryl root name indicates that at least one nitrogen, oxygen or sulfur atom, respectively, is present as a ring atom. The nitrogen atom of the heteroaryl may be optionally oxidized to the corresponding N-oxide. Non-limiting examples of suitable heteroaryl groups include pyridinyl, pyrazinyl, furanyl, thiophenyl, pyrimidinyl, isoxazolyl, isothiazolyl, oxazolyl, thiazolyl, pyrazolyl, furazanyl, pyrrolyl, pyrazolyl, triazolyl, 1,2,4-thiadiazolyl, pyrazinyl, pyridazinyl, quinoxalinyl, 2,3-naphthyridinyl, imidazo[1,2-a]pyridinyl, imidazo[2,1-b]thiazolyl, benzofurazanyl, indolyl, azaindolyl, benzimidazolyl, benzothiophenyl, quinolinyl, imidazolyl, thienopyridinyl, quinazolinyl, thienopyrimidinyl, pyrrolopyridinyl, imidazopyridinyl, isoquinolinyl, benzazaindolyl, 1,2,4-triazinyl, benzothiazolyl, and the like.

[0064] In the present invention, the term "amino" refers to a -NR'R" group. The amino group may be optionally substituted. In an unsubstituted amino group, R' and R" are hydrogen. In a substituted amino group, R' and R" may each independently be, but are not limited to, hydrogen, alkyl, heteroalkyl, cycloalkyl, heterocycloalkyl, alkylcycloalkyl, alkylheterocycloalkyl, alkoxy, sulfonyl, alkenyl, alkanoyl, aryl, arylalkyl or heteroaryl, provided that R' and R" are not both hydrogen. In a substituted amino group, R' and R" may be cyclized to form a cyclic amino group, such as a pyrrolidinyl or piperidinyl group. Such cyclic amino groups may incorporate other heteroatoms, for example to form piperazine or morpholine groups. Such cyclic amino groups may be optionally substituted, for example, by amino, hydroxyl or oxo groups.

[0065] In the present invention, the term "alkoxy" refers to -O-alkyl. Alkoxy can refer to a straight chain, branched or cyclic, saturated or unsaturated oxy-hydrocarbon chain, including, for example, methoxy, ethoxy, propoxy, isopropoxy, butoxy, tert-butoxy and pentoxy. Alkoxy can be optionally substituted with one or more alkoxy substituents ("substituted alkoxy").

[0066] In the present invention, the term "cycloalkyl" refers to a non-aromatic mono- or polycyclic ring system, and the preferred cycloalkyl ring contains about 5 to about 7 ring atoms. The cycloalkyl group may be optionally substituted with one or more "ring system substituents", which may be the same or different and are defined as above. Non-limiting examples of suitable monocyclic cycloalkyls include cyclopropyl, cyclopentyl, cyclohexyl, cycloheptyl, etc. Non-limiting examples of suitable polycyclic cycloalkyls include 1-decalinyl, norbornyl, adamantyl, etc. In the present invention, the term "cycloalkoxy" refers to a group in which one or more carbons in a mono- or polycyclic ring system of a "cycloalkyl" are replaced by oxygen atoms.

[0067] In the present invention, the term "heterocyclyl" refers to a non-aromatic saturated monocyclic or polycyclic ring system, wherein one or more ring atoms in the ring system are elements other than carbon, such as nitrogen, oxygen or sulfur, either alone or in combination. There are no adjacent oxygen and / or sulfur atoms in the ring system, and preferred heterocycles contain about 5 to about 6 ring atoms. The prefix aza, oxa or thia before the heterocyclyl root name indicates that at least one nitrogen, oxygen or sulfur atom is present as a ring atom, respectively. The heterocyclyl may be optionally substituted with one or more "ring system substituents", which are the same or different and are defined herein. The nitrogen or sulfur atom of the heterocyclyl may be optionally oxidized to the corresponding N-oxide, S-oxide or S, S-dioxide. Non-limiting examples of suitable monocyclic heterocyclyl rings include piperidinyl, pyrrolidinyl, piperazinyl, morpholinyl, thiomorpholinyl, thiazolidinyl, 1,3-dioxolane, 1,4-dioxacyclohexyl, tetrahydrofuranyl, tetrahydrophenylthio, tetrahydrothiopyranyl, etc.

[0068] like Figure 1As shown, the present invention provides a method for preparing modified aramid fiber, including surface complexation reaction and surface grafting reaction; the surface complexation reaction requires the use of a complex, and the role of the complex is to introduce Cl functional groups to form a new chemical surface. In the present invention, the complex comprises at least one having a chemical formula MCl x Compound, x is selected from an integer of 1-4, M is selected from Li, Ca, Al, Ga, In, Sn, Sb, Ti, Mn, Fe, Ni, Co or Cu; the surface grafting reaction requires the use of a coupling agent, the role of the coupling agent is to introduce active chemical groups, reduce the polarity of the fiber surface, and enhance the chemical activity and roughness of the fiber surface. In the present invention, the coupling agent is a compound having the following structural formula:

[0069]

[0070] T1 is selected from Si, Ti or Al; n1 is selected from an integer of 1-5;

[0071] n1 A's are the same as or different from each other, and A is selected from a halogen atom, a hydroxyl group, a nitro group, a cyano group, an amino group, a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C1-C10 cycloalkyloxy group, a substituted or unsubstituted C3-30 cycloalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted 3-30-membered heterocyclyl group, a substituted or unsubstituted 5-30-membered heteroaryl group, or a substituted or unsubstituted 3-30-membered ring formed by bonding with an adjacent substituent;

[0072] n1 R1s are the same as or different from each other, and R1 is selected from a direct bond, a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, or a substituted or unsubstituted C1-C10 cycloalkoxy group;

[0073] n1 T2 are the same or different from each other, and T2 is selected from a direct bond, an alkoxy group, a carboxyl group, a sulfoxy group, a phosphoryl group, a phosphite group or a pyrophosphoryl group;

[0074] R2 is selected from a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C1-C10 cycloalkyloxy group, a substituted or unsubstituted C3-30 cycloalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted 3-30 membered heterocyclyl group, or a substituted or unsubstituted 5-30 membered heteroaryl group; R3 is selected from a direct bond or a substituted or unsubstituted C1-C30 alkyl group.

[0075] In some embodiments of the present invention, the coupling agent is a compound having the following structural formula:

[0076]

[0077] wherein A2 is selected from a halogen atom, a hydroxyl group, a nitro group, a cyano group, an amino group, a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C1-C10 cycloalkyloxy group, a substituted or unsubstituted C3-30 cycloalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted 3-30 membered heterocyclyl group, a substituted or unsubstituted 5-30 membered heteroaryl group, or a substituted or unsubstituted 3-30 membered ring formed by bonding with an adjacent substituent;

[0078] R7 is selected from a direct bond, a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, or a substituted or unsubstituted C1-C10 cycloalkoxy group;

[0079] R4, R5 and R6 are each independently selected from a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C1-C10 cycloalkoxy group, a substituted or unsubstituted C3-30 cycloalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted 3-30 membered heterocyclyl group or a substituted or unsubstituted 5-30 membered heteroaryl group.

[0080] Preferably, the complex is selected from CaCl2 and / or LiCl2; further preferably, the complex is selected from CaCl2.

[0081] Preferably, the coupling agent is selected from silane coupling agent KH550 and / or silane coupling agent KH560; further preferably, the coupling agent is selected from silane coupling agent KH550.

[0082] In some embodiments of the present invention, the product obtained in step 2 is added to the second mixed solution, and the mixture is immersed for 2-3 hours and then dried.

[0083] In the present invention, the modified asphalt comprises base asphalt, which may be No. 70 base asphalt and / or No. 90 base asphalt, but is not limited thereto.

[0084] In the present invention, the modified asphalt includes a modified material, which may be SBS, SEBS, rubber, etc., but is not limited thereto.

[0085] In the present invention, the mix proportions of modified asphalt include fine-grained type (AC-13, AC-20, etc.), dense skeleton structure type (SMA-10, SMA-13, etc.), large pore open-graded drainage type (OGFC-13, OGFC-20, etc.).

[0086] In the present invention, a method for preparing modified aramid fiber is provided, and the method comprises the following steps: adding an appropriate amount of anhydrous CaCl2 particles or solution to an anhydrous ethanol solution to prepare a CaCl2 ethanol solution with a mass concentration of 5wt%. Then, bundled aramid fibers are added and the fibers are evenly dispersed using a stirring rod so that the fibers are fully in contact with the solution. After soaking for 8 to 40 hours, the wet fibers are filtered to obtain wet fibers, and then placed in a ventilation oven at a temperature of 85°C to 105°C and dried for 1.5h to 3h to obtain preliminary complexation reaction fibers; a solution is prepared according to a ratio of anhydrous ethanol to water of 7:3, and an appropriate amount of silane coupling agent (KH550) is added to prepare a coupling agent hydrolysis solution with a mass concentration of 1wt% to 2wt%. Then, the dried preliminary complexation reaction fibers are placed, and after soaking for 2h to 3h, the filtering and drying operations in step 1 are repeated to obtain modified aramid fibers.

[0087] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.

[0088] Embodiment 1:

[0089] like Figure 2 As shown, Example 1 includes the following steps:

[0090] (1) providing aramid fiber; dissolving CaCl2 in anhydrous ethanol to obtain a first mixed solution, wherein the mass percentage of CaCl2 is selected from 5%, adding aramid fiber to the first mixed solution, soaking for 8 hours, filtering, and then placing in a ventilated oven at a temperature of 90° C. and drying for 2 hours;

[0091] (2) dissolving the silane coupling agent KH550 in a second organic solvent, wherein the second organic solvent is a solution of anhydrous ethanol and water in a mass ratio of 7:3, to obtain a second mixed solution, wherein the mass percentage of the silane coupling agent KH550 is selected from 1%, and adding the aforementioned product to the second mixed solution, soaking for 1.5 hours, filtering, and then placing in a ventilated oven at a temperature of 90° C. and drying for 2 hours to obtain a modified aramid fiber; the microscopic morphology of the aramid fiber before and after modification in Example 1 is as follows Figure 6 shown.

[0092] (3) The modified aramid fiber was used to prepare fiber asphalt mortar and fiber asphalt mixture at a mass ratio of 8%. Figure 7 shown.

[0093] Embodiment 2:

[0094] Example 2 has the same steps as Example 1, except that after adding aramid fiber to the first mixed solution, the solution is filtered after soaking for 16 hours.

[0095] Embodiment 3:

[0096] Example 3 has the same steps as Example 1, except that after adding aramid fiber to the first mixed solution, the solution is filtered after soaking for 24 hours.

[0097] Embodiment 4:

[0098] Example 4 has the same steps as Example 1, except that after adding the aramid fiber to the first mixed solution, the solution is filtered after soaking for 32 hours.

[0099] Embodiment 5:

[0100] Example 5 has the same steps as Example 1, except that after adding aramid fiber to the first mixed solution, the solution is filtered after soaking for 40 hours.

[0101] Embodiment 6:

[0102] Example 6 has the same steps as Example 3, except that in the second mixed solution, the mass percentage of the silane coupling agent KH550 is selected from 0.5%.

[0103] Embodiment 7:

[0104] Example 7 has the same steps as Example 3, except that in the second mixed solution, the mass percentage of the silane coupling agent KH550 is selected from 1.5%.

[0105] Embodiment 8:

[0106] Example 8 has the same steps as Example 3, except that in the second mixed solution, the mass percentage of the silane coupling agent KH550 is selected from 2%.

[0107] Comparative Example 1:

[0108] Comparative Example 1 is obtained by directly mixing the aramid fiber with asphalt without modifying the aramid fiber.

[0109] Comparative Example 2:

[0110] Example 2 has the same steps as Example 3, except that, in the second mixed solution, the mass percentage of the silane coupling agent KH550 is selected from 0, that is, no silane coupling agent is added.

[0111] Characterization experiments and performance experiments:

[0112] Infrared spectrum experiment: The infrared spectra of Examples 1-5 and Comparative Example 1 are as follows Figure 3 As shown in the figure, it can be seen that with the increase of time, the peak area of ​​-NH functional group gradually increases and basically reaches stability at 24h, which indicates that the release of -NH functional group of CaCl2 modified aramid has reached saturation under this condition.

[0113] The infrared spectra of Examples 3, 6-8 and Comparative Example 1 are as follows: Figure 4 As shown in the figure, it can be seen that with the gradual increase of the concentration of the modified solution, the FTIR graph of the fiber at 1030cm -1 The absorption intensity at 2727-3310cm gradually increases, and when the modified concentration reaches 1%, the modification effect reaches saturation. -1 The absorption peak intensity at 1100cm -1 The absorption intensity of -Si-O-Si- has changed, which means that although more KH550 molecules can be grafted on the fiber surface by continuing to increase the concentration of the modified solution, the formation effect of -Si-OR chemical bonds is general.

[0114] High temperature rheological properties experiment: The test uses the Kinexus rotational rheometer produced by Malvern, UK, with a torque range of 3nNm-250mNm, a frequency range of 1μHz-150Hz, and a temperature control range of -30℃-200℃. During the test, the asphalt is placed between two metal plates, and the upper plate rotates at an angular velocity ω, thereby generating a sinusoidal stress of the same angular velocity on the sample. The initial test temperature of the temperature scan is 52℃, and the test temperature is gradually increased by 6℃. The test is loaded at a frequency of 10rad / s until the sample rutting coefficient drops below 1. The rutting coefficient (G* / sinδ) and phase angle (δ) of the asphalt binder at different temperatures are obtained through the test.

[0115] The high temperature rheological properties of Examples 3, 6-8 and Comparative Example 1 are as follows: Figure 5 As shown, it can be seen that for the aramid fiber modified by the preparation method provided by the present invention, the fiber asphalt mortar containing it shows good high-temperature rheological properties, and when the concentration of the coupling agent surface grafting reaction solution is 1wt%, the high-temperature rheological properties are best.

[0116] High temperature anti-rutting performance experiment: The test specimens were made according to the optimal asphalt dosage obtained from the Marshall test. The test specimens were made by rolling 12 times with a load of 9kN at 105°C. The size was 300mm×300mm×50mm. Three test specimens were set with the same fiber content. The formed test specimens were cured at room temperature for 12 hours. Before the test, the test specimens were placed in a rutting constant temperature chamber at 60°C for 5 hours. The test wheel pressure was 0.7±0.05MPa and the test temperature was 60±0.5°C.

[0117] The high temperature anti-rutting performance test of Example 3 and Comparative Example 1 is as follows Figure 8 As shown, it can be seen that for the aramid fiber modified by the preparation method provided by the present invention, the fiber asphalt mortar containing it shows good high-temperature rutting resistance.

[0118] Low temperature crack resistance test: The Marshall semicircular bending test (SCB) was selected to evaluate the low temperature crack resistance of asphalt mixture. The specimens were formed by cutting Marshall specimens, and the specimen dimensions used were as follows: 101.6mm in diameter, 25mm in thickness, with a pre-cut of 15mm in depth and 4mm in width in the middle. Three low temperature test temperatures were set at -5℃, 0℃ and 5℃, and the specimens were loaded with a stable vertical displacement speed at a loading rate of 0.5mm / min.

[0119] The low temperature crack resistance test of Example 3 and Comparative Example 1 is as follows Fig. 9As shown in the figure, it can be seen from the load-displacement curve that the modified fiber does not greatly increase the maximum load of the asphalt mixture, but it greatly increases the displacement corresponding to the maximum load and the damage displacement. The modified fiber can improve the fracture toughness of the asphalt mixture, which may be related to the better chemical activity of the modified fiber. The interface between the unmodified fiber and the asphalt only has physical bite, while the modified fiber with a rough surface and chemical activity not only has better physical bite, but also has chemical bonding with the asphalt.

[0120] Combination Figure 5 , Figure 8 and Fig. 9 It can be seen that the surface of the modified aramid fiber is attached with activated functional groups that can react with asphalt molecules, and the dispersibility of the aramid fiber in asphalt is greatly enhanced; in addition, the rutting factor of the fiber asphalt mortar prepared by using the modified aramid fiber of the present invention at 64°C is increased by 46.2% at most, the dynamic stability of the fiber asphalt concrete using the modified recycled aramid fiber of the present invention is increased by 9%, and the fracture energy at -5°C is increased by 66.6%.

[0121] Aramid fiber oil absorption test: Take approximately equal amounts of samples from more than 5 different locations to form a 5.00g±0.10g fiber sample, and take 2 samples in total: Place the sample in a porcelain dish, dry it in an oven at 60℃±5℃ for more than 2h, and cool it in a desiccator; Place the beaker on the balance to zero; Place the dried sample in the beaker and weigh the mass m, accurate to 0.01g; Pour an appropriate amount of kerosene into the beaker to cover the top of the fiber by about 2cm, and then let it stand for more than 5min; Clean the sample sieve and weigh it. Take the mass m, accurate to 0.01g; place the sample sieve above the collecting container, gently pour the mixture in the beaker into the sample sieve, rinse the fibers in the beaker with kerosene, and carefully pour it into the sample sieve: Do not disturb the sample sieve during the operation: Install the sample sieve (containing fibers absorbed with kerosene) on the fiber oil absorption rate meter: Start the meter, and t will automatically stop after 10 minutes of sieve vibration; Remove the sample sieve, weigh the mass m of the sample sieve and the fibers absorbed with kerosene, accurate to 0.01g.

[0122] The oil absorption rate experiments of Examples 3, 6-8 and Comparative Example 1 are shown in Table 1:

[0123] Table 1

[0124] Example <![CDATA[m1 / g]]> <![CDATA[m2 / g]]> <![CDATA[m3 / g]]> Oil absorption rate / times Comparative Example 1 5.1060 117.0370 148.1330 5.09 Example 6 5.0410 117.4205 157.9480 7.04 Example 3 5.0565 117.2090 158.6330 7.19 Example 7 5.0845 117.3185 156.7790 6.76 Example 8 5.0210 117.2150 155.2305 6.57

[0125] It can be seen that compared with comparative example 1, the aramid fiber modified by the preparation method provided by the present invention exhibits good oil absorption capacity, and when the concentration of the coupling agent surface grafting reaction solution is 1wt%, that is, the oil absorption capacity of Example 3 is significantly better than that of other examples and comparative examples.

[0126] Marshall Index Experiment:

[0127] The comparison of Marshall index of fiber asphalt mixture of Example 3 and Comparative Example 1 is shown in Table 2.

[0128]

[0129] It can be seen that the fiber asphalt mortar containing the aramid fiber modified by the preparation method provided by the present invention exhibits excellent comprehensive properties.

Claims

1. A method for preparing modified aramid fiber, characterized in that: The method comprises the following steps: Step 1: Providing aramid fiber; Step 2: dissolving CaCl2 in anhydrous ethanol to obtain a first mixed solution, adding the aramid fiber to the first mixed solution, soaking at room temperature for 24-40 hours, and then performing a drying process; Step 3: dissolving the silane coupling agent KH550 in an ethanol aqueous solution to obtain a second mixed solution, and adding the product obtained in step 2 to the second mixed solution, soaking at room temperature for 1-4 hours and then performing a drying process to obtain the modified aramid fiber; in: The mass percentage of CaCl2 is 5%; The mass ratio of anhydrous ethanol to water in the ethanol aqueous solution is 7:3; The mass percentage of the silane coupling agent KH550 is 0.5%-1%.

2. The method for preparing modified aramid fiber according to claim 1, characterized in that: The method satisfies at least one of the following conditions: (1) The drying process is carried out at 85°C-105°C, and the drying time is selected from 1.5-3h; (2) The drying process is natural air drying.

3. A modified aramid fiber, characterized in that: The modified aramid fiber is obtained by the method for preparing the modified aramid fiber according to any one of claims 1 to 2.

4. A modified asphalt, characterized in that: The modified asphalt comprises the modified aramid fiber according to claim 3, as well as base asphalt and a modifying material.

5. The modified asphalt according to claim 4, characterized in that: Based on the total mass of the modified asphalt, the mass percentage of the modified aramid fiber is selected from 0.1%-10%.

6. Use of the method for preparing modified aramid fiber according to any one of claims 1 to 2 in asphalt roads.

Citation Information

Patent Citations

  • Asphalt pavement repair material and preparation method thereof

    CN105802041A

  • Efficient anti-aging modified asphalt

    CN106147255A

  • Chemical modification method for surface of aramid fiber and application of same in preparation of silver-coated aramid composite fiber

    CN105839402A

  • Method for enhancing adhesion between aramid fibers and epoxy resin

    CN107724077A

  • Surface modification method of aramid fiber

    CN110424150A